The complete mitochondrial genome of Xylotrechus namanganensis (Coleoptera: Cerambycidae). Issue 7 (3rd July 2022) - Yan, Zhengpeng; Zhang, Laibin; Xiao, Haibing; Yang, Minglu
Abstract: The complete mitochondrial genome of Xylotrechus namanganensis was sequenced. The genome size was 15, 565 bp, which consists of 13 protein-encoding genes, 22 tRNA-encoding genes, 2 rRNA-encoding genes and 1D-loop control region. The base composition of mitogenome was biased toward A + T content, of which was 73.21%. The phylogenetic tree based on complete mitogenome sequences revealed that T. namanganensis had a closer relationship with X. grayii .